2003
DOI: 10.1016/s0393-0440(02)00191-2
|View full text |Cite
|
Sign up to set email alerts
|

Construction of self-adjoint Berezin–Toeplitz operators on Kähler manifolds and a probabilistic representation of the associated semigroups

Abstract: Abstract. We investigate a class of operators resulting from a quantization scheme attributed to Berezin. These so-called Berezin-Toeplitz operators are defined on a Hilbert space of square-integrable holomorphic sections in a line bundle over the classical phase space. As a first goal we develop self-adjointness criteria for Berezin-Toeplitz operators defined via quadratic forms. Then, following a concept of Daubechies and Klauder, the semigroups generated by these operators may under certain conditions be re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 65 publications
(118 reference statements)
0
4
0
Order By: Relevance
“…(More precisely, Kontsevich's formula is an expansion of a certain Feynman integral at a saddle point, see Cattaneo and Felder [60].) Connections between Feynman path integrals, coherent states, and the Berezin quantization are discussed in Kochetov and Yarunin [152], Odzijewicz [189], Horowski, Kryszen and Odzijewicz [130], Klauder [149], Chapter V in Berezin and Shubin [33], Marinov [168], Charles [61], and Bodmann [41]. For a discussion of Feynman path integrals in the context of geometric quantization, see Gawedzki [98], Wiegmann [258], and Chapter 9 in the book of Woodhouse [263].…”
Section: Some Other Quantization Methodsmentioning
confidence: 99%
“…(More precisely, Kontsevich's formula is an expansion of a certain Feynman integral at a saddle point, see Cattaneo and Felder [60].) Connections between Feynman path integrals, coherent states, and the Berezin quantization are discussed in Kochetov and Yarunin [152], Odzijewicz [189], Horowski, Kryszen and Odzijewicz [130], Klauder [149], Chapter V in Berezin and Shubin [33], Marinov [168], Charles [61], and Bodmann [41]. For a discussion of Feynman path integrals in the context of geometric quantization, see Gawedzki [98], Wiegmann [258], and Chapter 9 in the book of Woodhouse [263].…”
Section: Some Other Quantization Methodsmentioning
confidence: 99%
“…On the path integral side, our approach is directly inspired by the Daubechies-Klauder [77,194,195,199,35,198] continuous-time regularised coherent state phase space approach to path integration, and the closely related Anastopoulos-Savvidou [11,12,13] analysis of decoherence functional in the Isham-Linden quantum histories approach. Both have shown that one can think of the underlying dynamical objects of respective theories (path integrals and decoherence functionals) as consisting of the hamiltonian evolution perturbed by the geometric structures on the space of quantum states.…”
Section: Local Quantum Information Dynamics In Algebraic and Path Int...mentioning
confidence: 99%
“…𝑝 2 `9 𝑞 2 q as the pinned Wiener measure (see [35] for a systematic mathematical treatment of these objects in terms of the Berezin-Toeplitz operators). The generalisation to a wide class of connections ∇ 𝐷 Ψ and local entropic priors (even if kept at the second order riemannian level of g 𝐷 ) asks for a systematic development of a technique of stochastic integration of random walks X on R 𝑛 associated with the Brownian motions on smooth manifolds ℳ, dim ℳ " 𝑛, that could systematically address the functional integration of the above geometric structures beyond the level of heuristic treatment that is standard for physicists.…”
Section: Curvature Measures Desynchronisation In the Multi-user Infer...mentioning
confidence: 99%
See 1 more Smart Citation